The Double-Edged Sword Effect of Abusive Supervision on Subordinates’ Innovative Behavior - Zhu, Jinqiang; Zhang, Bainan (Frontiers in Psychology, 2019)
Existing studies on the relationship between abusive supervision and innovative behavior do not present a united picture. Drawing up the antecedent-benefit-cost framework and social cognitive theory, we tried to explain the contradictory relationships between them based on the mediating mechanism. Results showed that abusive supervision discouraged subordinates innovative behavior through reducing subordinates’ psychological safety but promoted subordinates’ innovative behavior through enhancing challenge-related stress. Our findings illustrated the complex mediating process of abusive supervision’s impact on innovative behavior, presenting a complementary explanation of the contradictory relationship between abusive supervision and innovative behavior. Also, we validated antecedent-benefit-cost framework and social cognitive theory, and shed light on two specific psychological cognitive mechanisms of social cognitive theory in the leadership field.